Cultural Heritage Accounting for Participatory Governance: A Participatory Action Reseach in Pata'padang Village - Tanggulungan, Gustin; Sukoharsono, Eko Ganis; Djamhuri, Ali; Purwanti, Lilik (JPAS (Journal of Public Administration Studies), 2023)
The study analyzes the practices of community participation in the initiation of sustainable cultural-tourism development. It will examine the accounting process in this field. In participatory action research, academics, local social actor and local government were collaboratively working as research teams. Actions that are also research methods are FGDs, interviews, and a study tour. The result of the project was a list of cultural heritage as accounting information for the development of tourist attractions and the formation of the Tourist Awareness Group (Pokdarwis) institution which marks the establishment of cohesion among research participants. Data analysis involves thematic analysis and reflection. The research indicated that activities related to the accounting process can serve as a participatory governance mechanism when designed as a value-added process and facilitated by the government's willingness to accept community-initiated activities.